2000
DOI: 10.1515/cclm.2000.102
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Polymorphism and Serum Concentration in Alzheimer's Disease in Nine European Centres: the ApoEurope Study

Abstract: As part of the ApoEurope Project, apolipoprotein E (apo E) common polymorphism and serum concentration were determined in 489 Alzheimer's disease patients and 429 controls. Patients and controls were recruited through nine centres in eight European countries. Age, sex ratios and education levels of both case and control populations were similar, although discrete differences appeared between centres. The prevalence of the epsilon4 allele was higher in Alzheimer's disease than in controls (increased by 140%), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
39
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 33 publications
10
39
1
Order By: Relevance
“…[2][3][4] Several studies have reported on the association between plasma apoE levels and AD or cognitive impairment, but with opposing results (table 1). [5][6][7][8][9][10] In some cross-sectional studies, plasma apoE levels were similar in patients with AD and controls, [6][7][8] whereas others found lower plasma apoE levels in patients with AD. 9 On the contrary, an earlier study reported higher plasma apoE levels in patients with AD.…”
mentioning
confidence: 99%
“…[2][3][4] Several studies have reported on the association between plasma apoE levels and AD or cognitive impairment, but with opposing results (table 1). [5][6][7][8][9][10] In some cross-sectional studies, plasma apoE levels were similar in patients with AD and controls, [6][7][8] whereas others found lower plasma apoE levels in patients with AD. 9 On the contrary, an earlier study reported higher plasma apoE levels in patients with AD.…”
mentioning
confidence: 99%
“…Within Europe, different frequencies of the 4 allele have been shown between the northern and southern regions (12). As a result, in European studies by the ApoEurope project, some countries failed to show 4 prevalence in AD, and other countries presented very low levels of serum ApoE in both control and AD populations, in contrast to other countries (23). Additionally, the ApoE 4 allele was not found to be associated with AD in less developed countries, restricting this association to only western countries (46,47).…”
Section: Discussionmentioning
confidence: 95%
“…Even though the ApoE 4 allele has been well known to indicate higher susceptibility to developing AD, their relation is still debated (23,46,47). In addition, other polymorphisms such as the promoter/enhancer region of the ApoE gene have been suggested to be associated with AD (26 -28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations